(untitled) (Research, Society and Development, 2026)
Obesity in adolescence is an important public health issue due to its high prevalence and its clinical, psychosocial, and economic impacts throughout life. Therefore, this study aimed to analyze juvenile obesity in Brazil, addressing its determinants, consequences, and coping strategies. This is a qualitative-descriptive narrative review, conducted in 2025, based on articles published between 2020 and 2025 in the SciELO, PubMed, and LILACS databases, using descriptors related to eating behavior, body mass index, and eating habits. The results demonstrated that obesity in adolescence has a multifactorial etiology, being predominantly associated with exogenous factors such as excessive consumption of ultra-processed foods, sedentary lifestyle, influence of the family environment, and socioeconomic inequalities. A significant association was also observed with early metabolic alterations, such as dyslipidemia, hypertension, and insulin resistance, in addition to psychosocial impacts, including stigmatization, low self-esteem, and anxiety and depressive symptoms. The COVID-19 pandemic exacerbated this scenario, contributing to an increase in overweight in this age group. It is concluded that addressing obesity in adolescence requires integrated and sustained actions, involving educational strategies, multidisciplinary interventions, and public policies aimed at promoting healthy food environments and the early prevention of non-communicable chronic diseases.